Youth's potential of adopting the Mediterranean diet lifestyle in response to climate change: Empirical study in Crete, Greece - Kaouter Essakkat; Konstandinos Mattas; Ilkay Unay-Gailhard; George Baourakis (New Medit, 2021)
The Mediterranean diet is considered one of the healthier and most balanced dietary models currently in existence. Different studies suggest that it is environmentally friendly: it combines low greenhouse gas emissions, low demand of soil water and less deforestation. Climate change can be mitigated through what consumers decide to eat. This article addresses the issue of by studying the intention of young consumers to shift their diets towards the Mediterranean Diet to prevent climate change through face interviews, collected in Crete, Greece (N=287). Using the Theory of Planned Behavior, the objective is to identify whether attitudes, subjective norms and perceived behavioral control guide such a behavior. Our findings highlight that young consumers' perceived behavioral control have the highest influence on the intention, followed by their attitudes. As for the subjective norms, it has no significant impact on the intention
Keywords: D12; Q13; Q18; 330; young consumers; Mediterranean diet; climate change; Theory of Planned Behavior; Greece